2019
DOI: 10.1002/jcb.28722
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐206 overexpression inhibits epithelial‐mesenchymal transition and glomerulosclerosis in rats with chronic kidney disease by inhibiting JAK/STAT signaling pathway

Abstract: Chronic kidney disease (CKD) is a traumatic disease with significant psychic consequences to the patient's overall physical condition. microRNA‐206 (miR‐206) has been reported to play an essential role in the development of various diseases. The purpose of the present study is to investigate the effect of miR‐206 through the JAK/STAT signaling pathway on epithelial‐mesenchymal transition (EMT) of renal tubular epithelial cells and glomerulosclerosis in rats with CKD. The targeting relationship between miR‐206 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…JAK, which is a receptor-associated tyrosine kinase, acts as regulators of cytokine and growth factor signaling. JAK2 is a regulator of the profibrotic results of TGF-β in many fibrotic diseases ( O'Shea et al, 2015 ; Cao et al, 2019 ; Zhao et al, 2019 ; Qin et al, 2020 ). STAT3, a STAT protein and a downstream regulator of JAK2 signaling, is crucial to many fibrotic diseases in a TGF-β-dependent manner ( O'Shea et al, 2015 ; Chakraborty et al, 2017 ; Oh et al, 2018 ).…”
Section: Noncanonical Tgf-β Signaling Pathwaymentioning
confidence: 99%
“…JAK, which is a receptor-associated tyrosine kinase, acts as regulators of cytokine and growth factor signaling. JAK2 is a regulator of the profibrotic results of TGF-β in many fibrotic diseases ( O'Shea et al, 2015 ; Cao et al, 2019 ; Zhao et al, 2019 ; Qin et al, 2020 ). STAT3, a STAT protein and a downstream regulator of JAK2 signaling, is crucial to many fibrotic diseases in a TGF-β-dependent manner ( O'Shea et al, 2015 ; Chakraborty et al, 2017 ; Oh et al, 2018 ).…”
Section: Noncanonical Tgf-β Signaling Pathwaymentioning
confidence: 99%
“…STAT is widely involved in cell proliferation, apoptosis, and tumorigenesis, and is also related to the occurrence and development of a variety of diseases [13]. Activation of the JAK/STAT1 pathway can upregulate the expression of pro‐inflammatory factor interleukin (IL)‐1 and pro‐fibrotic factor tumor growth factor (TGF)‐β in the kidney; thus, STAT1 may be a potential therapeutic target for CKD [14]. Saraiva et al .…”
Section: Introductionmentioning
confidence: 99%
“…STAT is widely involved in cell proliferation, apoptosis, and tumorigenesis, and is also related to the occurrence and development of a variety of diseases [13]. Activation of the JAK/STAT1 pathway can upregulate the expression of pro-inflammatory factor interleukin (IL)-1 and pro-fibrotic factor tumor growth factor (TGF)-b in the kidney; thus, STAT1 may be a potential therapeutic target for CKD [14]. Saraiva et al revealed the association between a STAT1 gene polymorphism and the development of severe periodontitis, while Haftcheshmeh et al showed that STAT1 is upregulated in the periodontal tissue of patients with periodontitis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, unclear that how high glucose induces the expression of TGF-β1 and ECM accumulation. e JAK/ STAT pathway is a crucial signal transduction cascade that regulates cellular activation, proliferation, and inflammation, and the activation of the JAK/STAT-signaling pathway leads to the development of fibrosis in the lung and kidney via the induction of TGF-β1 and collagens [17,18]. A STAT3 inhibitor suppressed TGF-β1 so as to prevent the occurrence of DKD in STZ-induced rats [19], while it was also reported that JAK2/STAT3 signaling may play a role in the renal fibrosis repair process in mice with UUO (unilateral ureteral obstruction) and that this effect was partially mediated by MMP-2 activation.…”
Section: Discussionmentioning
confidence: 99%